The Effects of Service Quality on Tourist Loyalty Towards Malaysian Budget Hotels - Abdul Latif, Samshul Amry; Syed Nasir, Sharifah Nabiha; Matyakubov, Umidjon; Isaqov, Rasulbek (2023)
The hotel industry plays a vital role in tourism development by providing visitor accommodation facilities. This paper focuses on the effects of service quality on the budget hotel industry in Malaysia. Despite the increasing number of tourists opting for budget hotels in recent years, issues related to service quality have affected tourist satisfaction and loyalty, posing significant challenges for the budget hotel sector to maintain its business. The study analyzed the effects of service quality on tourist loyalty towards budget hotels and identified the most influential factor in service quality that affects tourist loyalty. A quantitative approach was employed in this study, and the findings indicate that the responsiveness quality dimension has the most significant effect on tourist loyalty. In contrast, assurance and reliability have no significant effects. Budget hotels must improve their service quality, specifically responsiveness, to enhance tourist loyalty and maintain their business in the highly competitive hotel industry.